Assessment of Amyloid Deposition in Patients With Probable REM Sleep Behavior Disorder as a Prodromal Symptom of Dementia With Lewy Bodies Using PiB-PET - Kobayashi, Ryota; Hayashi, Hiroshi; Kawakatsu, Shinobu; Okamura, Nobuyuki; Yoshioka, Masanori; Otani, Koichi (Frontiers in Neurology, 2019)
Introduction: Dementia with Lewy bodies (DLB) often exhibits REM sleep behavior disorder (RBD) at its prodromal stage. Meanwhile, DLB is often comorbid with Alzheimer’s disease (AD)-type pathology. In typical AD, amyloid-β deposition begins considerably before the onset of dementia and has already reached a plateau at the stage of mild cognitive impairment. However, it is not known when amyloid accumulation starts in DLB with AD-type pathology. In the present study, we examined amyloid deposition in patients with RBD as a prodromal symptom of DLB using [11C]-Pittsburgh compound B positron emission tomography (PiB-PET). Methods: The subjects were 12 patients with probable RBD as diagnosed by the Japanese RBD screening questionnaire. They also showed abnormality in 123I-metaiodobenzylguanidine myocardial scintigraphy, a biomarker for DLB. For comparison, 11 patients with probable DLB were included. Applying PMOD software to the PiB-PET images, the global cortical distribution volume ratio was calculated and a ratio >1.3 was regarded as PiB-positive. Results: Two of the RBD patients (16.7%) and eight of the DLB patients (72.7%) were PiB-positive. The amyloid-positive rate was significantly lower in the RBD group than in the DLB group (P = 0.012). Conclusion: The prevalence of amyloid deposition in RBD as a prodromal symptom of DLB was significantly lower than that in DLB, suggesting that amyloid accumulation does not begin at the early stage of DLB.